Lesinurad Combined With Allopurinol: A Randomized, Double‐Blind, Placebo‐Controlled Study in Gout Patients With an Inadequate Response to Standard‐of‐Care Allopurinol (a US‐Based Study). Issue 1 (January 2017) - Saag, Kenneth G.; Fitz‐Patrick, David; Kopicko, Jeff; Fung, Maple; Bhakta, Nihar; Adler, Scott; Storgard, Chris; Baumgartner, Scott; Becker, Michael A.
Abstract : Objective: Lesinurad is a selective uric acid reabsorption inhibitor used for the treatment of gout in combination with a xanthine oxidase inhibitor. The Combining Lesinurad with Allopurinol Standard of Care in Inadequate Responders (CLEAR 1) study, a 12‐month, multicenter, randomized, double‐blind, placebo‐controlled phase III trial, was conducted to investigate daily lesinurad (200 mg or 400 mg orally) added to allopurinol versus placebo plus allopurinol in patients with serum urate (UA) levels above a target of <6.0 mg/dl. Methods: Patients receiving ≥300 mg of allopurinol (≥200 mg in those with moderate renal impairment) who had serum UA levels ≥6.5 mg/dl at screening and ≥2 gout flares during the previous year were studied. The primary end point was the proportion of patients achieving a serum UA level of <6.0 mg/dl at month 6. Key secondary end points were the mean gout flare rate requiring treatment (months 7–12) and the proportions of patients with complete resolution of ≥1 target tophus (month 12). Safety assessments included adverse events and laboratory data. Results: The study patients (n = 603) were predominantly male and had a mean ± SD age of 51.9 ± 11.3 years, a gout duration of 11.8 ± 9.4 years, a baseline serum UA level of 6.94 ± 1.27 mg/dl, and were receiving an allopurinol dosage of 306.6 ± 59.58 mg/day. Lesinurad at doses of 200 mg or 400 mg added to allopurinol therapy significantly increased the proportions of patients who achieved serum UA target levels by month 6 as compared with those receiving allopurinol alone (54.2%, 59.2%, and 27.9%, respectively, P < 0.0001). Lesinurad was not significantly superior to allopurinol alone in terms of the secondary end points: rates of gout flares and complete resolution of tophi. Lesinurad was generally well‐tolerated; the safety profile of the 200‐mg dose was comparable to that of allopurinol alone, except for higher incidences of predominantly reversible elevations of serum creatinine levels. Conclusion: Lesinurad added to allopurinol provided benefit as compared with allopurinol alone in reducing serum UA levels and represents a new treatment option for patients needing additional urate‐lowering therapy.